Novel Modulation Recognition for WFRFT-Based System Using 4th-Order Cumulants - Yuan Liang; Xin Xiang; Ye Sun; Xinyu Da; Cong Li; Liyan Yin (IEEE Access, 2019)
We present a novel modulation recognition for weighted-type fractional Fourier transform (WFRFT)-based systems using the fourth-order cumulants. First, the constellation characteristics of the basic digital modulations ASK, PSK, and QAM are analyzed, and the corresponding relationships between the neighboring constellation points' distance and the constellation size are deduced. Second, the closed-form expressions of the fourth-order cumulants (C42) for the WFRFT-based systems with ASK, PSK, and QAM are derived. Finally, through the first- and second-order derivatives of the C42, we prove that the optimal WFRFT order αr can be obtained through the minimization of the C42. The simulation results show that the novel recognition for the WFRFT-based system is feasible and can reach an accuracy of almost 90% when energy per bit-to-noise power spectrum density ratio (Eb/N0) is greater than 6.